2021
DOI: 10.3390/diagnostics11060938
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Lumbar Disc Herniation with Lumbar Volumetric Bone Mineral Density in a Cross-Sectional Chinese Study

Abstract: Little is known about the effect of lumbar intervertebral disc herniation (LDH) on lumbar bone mineral density (BMD), and few previous studies have used quantitative computed tomography (QCT) to assess whether the staging of LDH correlates with lumbar vertebral trabecular volumetric bone mineral density (Trab.vBMD). To explore the relationship between lumbar Trab.vBMD and LDH, seven hundred and fifty-four healthy participants aged 20–60 years were enrolled in the study from an ongoing study on the degeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…11 Additionally, it has been conjectured that there is no significant association between osteoporosis and IVD degeneration. 12 Therefore, the association between osteoporosis and IVD degeneration remains controversial and unclear, and the mechanism of interaction between osteoporosis and IVD degeneration needs to be elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Additionally, it has been conjectured that there is no significant association between osteoporosis and IVD degeneration. 12 Therefore, the association between osteoporosis and IVD degeneration remains controversial and unclear, and the mechanism of interaction between osteoporosis and IVD degeneration needs to be elucidated.…”
mentioning
confidence: 99%
“…For example, a study of postmenopausal women in Finland revealed an association between higher lumbar spine bone mineral density (BMD) and more severe IVD degeneration, 10 and a study by Wang et al showed that severe IVD degeneration was more severe in postmenopausal women than in men and that a lower BMD was associated with less severe IVD degeneration 11 . Additionally, it has been conjectured that there is no significant association between osteoporosis and IVD degeneration 12 . Therefore, the association between osteoporosis and IVD degeneration remains controversial and unclear, and the mechanism of interaction between osteoporosis and IVD degeneration needs to be elucidated.…”
mentioning
confidence: 99%
“…Regarding potential associations between the degenerative spine and BMD, Geng et al investigated 745 participants (aged 20 to 60 years) by MRI to assess disc herniations and by dedicated quantitative CT (QCT) to extract BMD (L2–4) [ 25 ]. According to the results of their study, the differences in BMD between subjects without and those with single or ≥2 sites of lumbar disc herniation were not statistically significant, and no associations between BMD and lumbar disc herniation were observed in either men or women [ 25 ].…”
mentioning
confidence: 99%
“…1 Although studies have proposed evidence supporting a relationship between sex hormones, menopause, and intervertebral disc (IVD) degeneration, 2,3 the association between osteoporosis and IVD degeneration is controversial. 4 Pathophysiological processes such as the conversion of hematopoietic cells to adipocytes have been extensively shown to be fundamental to the pathway to osteoporosis. 5 Although the classical Pfirrmann grading system has been identified to be highly subjective, previous studies have explored this system to evaluate pathological changes.…”
mentioning
confidence: 99%
“…This disease is characterized by bone mass reduction, bone tissue microstructural degeneration, and increased susceptibility to fracture 1 . Although studies have proposed evidence supporting a relationship between sex hormones, menopause, and intervertebral disc (IVD) degeneration, 2,3 the association between osteoporosis and IVD degeneration is controversial 4 …”
mentioning
confidence: 99%